Let your hair down [compact disc] (Loud & Proud Records/Roadrunner Records, 2011)
The Steve Miller Band follows up the success of 2010's Bingo with a new album that features some of the last recordings by Norton Buffalo, a longtime collaborator and master harmonica player. He saved the most bluesy, rocking, best guitar playing tracks for this second serving of blues rock. This must-have CD includes the songs Just a Little Bit and Sweet Home Chicago.